KNOWLEDGE, ATTITUDE, AND BEHAVIOR OF THE ELDERLY TOWARDS THE IMPLEMENTATION OF COVID-19 VACCINATION IN SOUTH NIAS, INDONESIA: A CROSS SECTIONAL STUDY - Purba, Ivan Elisabeth; Sihura, Irene Rostiana; Tarigan, Yenni Gustiani (Jurnal Ilmiah Keperawatan, 2024)
Despite the susceptibility of the elderly to COVID-19, vaccination coverage in this age group is still far from Indonesia's national target. This research studied the implementation of the COVID-19 vaccine in Teluk Dalam, South Nias District, in 2021 and analyzed the relationship between knowledge, attitudes, and behaviour of the elderly towards implementing vaccination. It was a mixed-method study with an explanatory design. The population of this study included the elderly in Teluk Dalam, with a total of 33 people serving as research samples and three informants for qualitative data. Data were obtained by administering questionnaires and interviews, analyzed by the SPSS statistical tool with chi-square test at α = 5%, and compared with the collected qualitative data. The results showed that the elderly in Teluk Dalam's knowledge of implementing the COVID- 19 vaccine was still low, with negative attitudes and behaviour. There was a significant relationship between knowledge, attitudes and behaviour of the elderly towards implementing COVID-19 vaccination in Teluk Dalam, South Nias District (p <0.05). It is recommended that the elderly attend counselling given by health workers so that they can increase their knowledge about the implementation of the COVID-19 vaccination and change their attitude and behaviour and want to take part in the COVID-19 vaccination and health workers to provide information about the implementation of the COVID-19 vaccine to the public, especially the elderly more specific.